2011
DOI: 10.4061/2011/527137
|View full text |Cite
|
Sign up to set email alerts
|

Nephronophthisis: A Genetically Diverse Ciliopathy

Abstract: Nephronophthisis (NPHP) is an autosomal recessive cystic kidney disease and a leading genetic cause of established renal failure (ERF) in children and young adults. Early presenting symptoms in children with NPHP include polyuria, nocturia, or secondary enuresis, pointing to a urinary concentrating defect. Renal ultrasound typically shows normal kidney size with increased echogenicity and corticomedullary cysts. Importantly, NPHP is associated with extra renal manifestations in 10–15% of patients. The most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 91 publications
(156 reference statements)
1
38
0
Order By: Relevance
“…[2][3][4][5][6][7] The nephronophthisis (NPHP) types 1-11 and NPHPL1 comprise a less common group of autosomal recessive disorders, but they are collectively the leading genetic cause of ESRD within the first 3 decades of life. [8][9][10] We previously reported that the mouse juvenile cystic kidneys (jck) model of recessive polycystic kidney disease (PKD) is due to a missense mutation in the Nek8 gene; jck animals develop cysts in distal nephron segments and collecting ducts within the first week of life and the disease rapidly progresses, causing renal failure and death by 6 months of age. 11 Nek8 encodes a highly conserved member of the Nek family of serine/threonine kinases, characterized by an N-terminal kinase domain homologous to that of the Aspergillus nidulans NIMA protein that controls cell cycle entry during mitosis.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] The nephronophthisis (NPHP) types 1-11 and NPHPL1 comprise a less common group of autosomal recessive disorders, but they are collectively the leading genetic cause of ESRD within the first 3 decades of life. [8][9][10] We previously reported that the mouse juvenile cystic kidneys (jck) model of recessive polycystic kidney disease (PKD) is due to a missense mutation in the Nek8 gene; jck animals develop cysts in distal nephron segments and collecting ducts within the first week of life and the disease rapidly progresses, causing renal failure and death by 6 months of age. 11 Nek8 encodes a highly conserved member of the Nek family of serine/threonine kinases, characterized by an N-terminal kinase domain homologous to that of the Aspergillus nidulans NIMA protein that controls cell cycle entry during mitosis.…”
mentioning
confidence: 99%
“…After genetic counselling by geneticist, blood may be sent for genetic testing (Fig. 2) [16]. Gene analysis (with emphasis on the variants within 23 genes known to be involved in nephronophthisis and related ciliopathies) in this case revealed homozygous NPHP 1 gene deletion that is similar with NPHP 1 associated JSRD, but previous different studies demonstrated the presence of MTS on cerebral imagings in all of the cases of NPHP 1 associated JRSD [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 82%
“…37,83 Other syndromes that may have concurrent NPHP include congenital ocular motor apraxia type Cogan, cognitive impairment, phalangeal cone-shaped epiphyses in MainzerSaldino syndrome, Bardet-Biedl syndrome, Ellis-van Creveld syndrome, Jeune asphyxiating thoracic dystrophy, Alström syndrome, and Meckel-Gruber syndrome (MKS). 1,32,33,83,92 Given the low penetrance of many of these phenotypes and the small number of mice and limited time points that we examined, it is possible that some of these lesions could be linked to TMEM218 deficiency in mice in the future. In our experience, the appearance of very similar phenotypes (phenocopies) in either mice or humans with mutations in different genes often indicates that the proteins encoded by these mutant genes involve different steps in a common metabolic pathway or affect the same process or structure.…”
Section: Discussionmentioning
confidence: 99%